Endometrial stromal sarcoma—A retropsective analysis of factors affecting recurrence. (September 2017) - Agarwal, Reshu; Rajanbabu, Anupama; Nair, Indu R.; Satish, Chandramouli; Jose, Georgeena; Unikrishnan, U.G.
Abstract: Objective: To assess the factors associated with disease free survival and overall survival in endometrial stromal sarcoma (ESS). Methods: This was a single institution retrospective analysis done at Amrita Institute of Medical Sciences. Records from January 2005 to October 2016 were analysed and 42 patients with ESS were identified. Clinicopathological, surgical management, adjuvant treatment and outcome data were collected. Disease free and overall survivals were analysed using Kaplan-Meier method and compared using log rank test. Results: Out of 38 patients included in analysis 28 (73.7%) had low grade ESS (LGESS) and 10 (26.3%) had high grade ESS (HGESS). The median follow up period was 28 months (range 1–110 months). The 5 year disease free survival (DFS) and overall survival (OS) for the entire cohort were 62.9 and 89.1% respectively. High grade ESS was significantly associated with recurrence on univariate analysis ( p = 0.045). Complete staging surgery in both HGESS and LGESS and adjuvant treatment in HGESS and advanced stage LGESS (cohort 1) were associated with improved 5-year DFS of 90.9% ( p < 0.001). Completion staging surgery in patients with initial incomplete surgery (cohort 3) was associated with improved 5-year DFS of 100% ( p < 0.001). Complete Staging surgery but no adjuvant treatment in HGESS and advanced stage LGESS (cohort 2) was associated with significantly poor 2-year DFS of 20% (5-year DFS rate 0%; as all patients recurred within 27 months) (P < 0.001). Significantly reduced 5-year DFS rate of 25% ( p < 0.001) was also seen in cases where initial incomplete surgery was not followed by complete staging and adjuvant treatment (cohort 4). Adjuvant treatment in HGESS was associated with improved 5-year DFS of 66.7% ( p = 0.043). Resection of recurrent lesions were associated with improved mean survival of 41.2 months. Conclusion: Incomplete surgery and no adjuvant treatment in ESS are associated with poor DFS. Complete staging surgery is associated with improved DFS. Resection of recurrent disease is associated with survival advantage.